Iron working in Anglo-Saxon England: New evidence to show fresh iron smelting of ironstone ores from the 6th–10th centuries CE. (June 2018) - Hall, Neil
Abstract: This paper discusses the current recycling and importation models of the Early Saxon iron economy. New evidence from the analysis of smelting slags and ores from the sites of Quarrington and Flixborough is presented which proves that fresh metal production was also occurring at this time, and with an increase in scale through the Saxon period. The findings are further supplemented by historical evidence which demonstrates that bedded iron ores were in use from at least the 7th century CE Highlights: Bog ore and ironstone were in use at Flixbrough from the 6th century CE Quarrington smelters exploited a geological bedded ore as suggested by phosphorus content. These analyses demonstrate that the Early Saxon iron economy was not reliant upon scavenging scrap metal.